EXPLORING THE NUTRIENT POTENTIAL OF NYMPHAEA ALBA (WATER LILLY), FOR USE AS LIVESTOCK FEED - Abarike, E. D; Amenyogbe, E.; Ampofo-Yeboah, A.; Abobi, S. M.; Atindaana, S. A.; Alhassan, E. H.; Akongyuure, D. N. (UDS International Journal of Development, 2016)
The study aimed at finding the nutrient composition of Nymphaea alba to help control the growth of the aquatic plant as it hinders the livelihoods of people who use the Banka dam for fishing and irrigation. The leaves, leaf stalks and flowers ofÂ Nymphaea alba were sampled toÂ determine the crude protein, crude fibre, the nitrogen free extract, ether extract, total ash and some minerals. The study revealed that, the leaf stalks of the plant has significantly (P < 0.05) more ash (19.25 % - 20.59 %) than there is in the leaves and flowers with the leaves significantly (P < 0.05) richer in protein (20.91% - 25.40 %). Fibre concentration was highest in leaf stalks (12.84 % - 15.14 %) with low levels of ether extracts (1.10 % to 3.82 %) in the entire plant. Nymphaea alba is rich in nitrogen free extract (53.09 % - 56.57 %) in all of its parts, thus the leaf stalks, leaves and flowers.Â Potassium (1.56 % â€“ 4.63 %) and sodium (1.97 % - 4.21 %) were the dominant minerals with calcium, zinc, iron and copper equally present in Nymphaea alba in all of its parts investigated. The respective levels of crude protein, fibre, nitrogen free extract, lipids, ash and minerals are adequate for use as feed for livestock. However, there is the need for studies on palatability and digestibility of the aquatic plant as these affect utilization by livestock. Keywords:Â Nymphaea alba, crude fibre, crude protein, nitrogen free extract, mineral